Research on application of pyrolysis technology to convert plastic waste into liquid fuel - Minh Quoc Binh Phan; Chi Trung Duong; Van Long Le; Thi Quynh Chau Mai (Petrovietnam Journal, 2025)
Plastic waste pollution has become increasingly severe in Vietnam, particularly in the Southern region, which generates the country’s largest amount of plastic waste. Although the rate of municipal waste collection is high, about 90% in each province, source separation is virtually not implemented. Valuable plastics are informally collected for recycling, while the remainder - comprising predominantly low-quality mixed plastics, accounting for 5 - 8% of waste by weight - ends up in landfills. The research analyzed the status of plastic waste in Vietnam, surveyed the waste plastic flow in southern provinces, and compared existing treatment technologies. Results show that mechanical recycling helps reuse materials but is limited by feedstock quality; meanwhile, pyrolysis and gasification can convert mixed plastics into liquid fuels, olefins, or synthesis gas, providing higher value. Based on technical and economic criteria, pyrolysis technology was selected for the project due to its high feasibility, low operational risk, and scalability, making it suitable for Vietnam's current conditions. Regarding implementation sites, the research team proposed several centralized waste treatment zones in the Southeast region - areas characterized by abundant waste sources, existing infrastructure, and investment support policies - and discussed the challenges associated with project deployment.